The interfacial mechanical properties of functionalized graphene–polymer nanocomposites. Issue 71 (13th July 2016) - Liu, Feng; Hu, Ning; Zhang, Jianyu; Atobe, Satoshi; Weng, Shayuan; Ning, Huiming; Liu, Yaolu; Wu, Liangke; Zhao, Youxuan; Mo, Fuhao; Fu, Shaoyun; Xu, Chaohe; et al.
Abstract : The interfacial mechanical properties between graphene (GR) and a polymer matrix play a key role in load transfer capability for GR/polymer nanocomposites. Abstract : The interfacial mechanical properties between graphene (GR) and a polymer matrix play a key role in load transfer capability for GR/polymer nanocomposites. Grafting of polymer molecular chains on GR can improve the dispersion of the GR in a polymer matrix and change the interfacial mechanical properties between the GR and the polymer matrix. In this work, we investigated the interfacial mechanical properties between GR functionalized with polymer molecular chains and a polyethylene (PE) matrix using molecular dynamics simulations. The influences of grafting density and chain length on the interfacial mechanical properties were analyzed. The results show that grafting of short PE molecular chains on GR can significantly improve the interfacial shear strength and interfacial Mode-II fracture toughness in functionalized GR/PE nanocomposites.